Review of seismicity and other geophysical data near Nares Strait - Wetmiller, Robert J.; Forsyth, David A. (Meddelelser om Grønland. Geoscience, 1982)
Nares Strait is aseismic even to small magnitude levels, in contrast to nearby active areas in Baffin Bay, the Lincoln Sea and the Sverdrup Basin. Activity immediately to the south of the Strait is infrequent and minor. The nature of Lg propagation suggests a discontinuity in the continental crust at the southern terminus of Nares Strait while seismicity in the Lincoln Sea seems most logically related to an extension of the activity in the Sverdrup Basin. Intense seismic activity in Baffin Bay appears to be confined south of latitude 75°N. Focal mechanisms for recent earthquakes in Baffin Bay and north of Greenland do not support the hypothesis of large left-lateral displacements along Nares Strait. Free air gravity anomalies indicate that some of the seismicity of northern Baffin Bay and Baffin Island may be related to glacial rebound or uncompensated sedimentary loads acting on zones of weakness. The aseismic nature of Nares Strait under the action of stresses due to local glacial unloading or regional north-south compression argues against the presence of a relatively young shear zone of major crustal or lithospheric dimension.